Does partial concealment influence predation attempts on small model snakes in South Africa?. Issue 1 (9th August 2019) - Coombs, Gareth
ABSTRACT: Predation risk may be high in small snakes and most small snakes are thought to avoid certain behaviours, such as basking in open areas to reduce predation risk. The extent to which this concealment limits predation during basking is not known, but available data suggests that such concealment may significantly reduce predation attempts. Using model snakes placed in the field, predation rates on small model snakes were tested, specifically whether attack rates differ between partially concealed model snakes and model snakes placed in open unconcealed positions. Results from the current study support previous studies that predation pressure was high (average = 22.15%), but was not significantly reduced by semi-sheltered basking. An important new finding of this study was the high number of model snakes that experience trampling by wild ungulates (average = 12.72%.) This suggests that snakes basking in open and sheltered areas are also at risk of being killed or injured through trampling by larger animals. This study makes an important contribution to understanding predation pressure in African snakes and highlights other threats that snakes are exposed to during basking and thermoregulation.